Komunikasi Interaktif Grup Facebook Komunitas Suwec Startup Ekonomi Kreatif - Rahardi, Rachmad (Jurnal Komunikasi Profesional, 2018)
In order to control the numbers of a Surabaya’s population whose numbers are increasing every year,the Surabaya City Government implementsFamily Planning program. Currently, family planning program has run well and 99.74% of the acceptors are women (wives). Whereas for families whose wives have problems with various family planning methods, they choose not to use family planning program.  To encourage the number of acceptors of male family planning programs, the Surabaya City government will launch an advertisement about it. To support the effectiveness of these advertisements, the emotions of the male receptors is studied. The results show that the positive emotions when using male contraception were 79%. Emotions with the highest valuesshould be considered when designing ads.Keywords:Emotion, Family Planning Program, Man FP